Reducing Variability of Workforce as a Tool to Improve Plan Reliability. (2017) - Shen, Yicheng; Zygmunt, Katarzyna Julia; Wandahl, Søren
Abstract: Variability of flow is recognized as one of the greatest obstacles to production management. Since the work flow and labour flow are two dominators of work performance, it is important to manage them simultaneously. The objective of this paper is to examine if an increased plan reliability could be reached by reducing the variance of a labour flow. Therefore, three different construction labour data sets have been examined by utilizing Monte Carlo Simulation, to analyze the probability to finish simulated projects within a certain time. The research findings revealed that reducing variance of the workforce flow does not necessarily shorten the project length, nevertheless it increases probability to finish the tasks within a critical path duration. Additionally, it was concluded, that reducing the variance of crew allocation can improve the productivity.